Natural Time and Bureaucratic Time: State Building, Forests and Environmental Conflicts in the 1800s. (1st August 2019) - Bonan, Giacomo
Historians traditionally consider the Napoleonic period a key point in the process of state centralisation in most of continental Europe. This is certainly true of the legislative and administrative transformations overseen by state authorities during that epoch. However, there is still much to learn about the consequences of these changes on the ground, especially in peripheral regions. In this respect, an environmental history approach can provide new perspectives on the growing presence of state authorities in the management of environmental resources and associated struggles in rural areas. In this article, I analyse the reactions of some alpine communities to state intervention in the years following the implementation of Napoleonic reforms. The lens through which these interactions are observed is that of valorisation of forest resources, which were the economic lynchpin of alpine communities and, at the same time, a strategic issue for state authorities.